IgG4‐related sclerosing cholangitis, a mimicker of the cholangiocarcinoma: A case report. Issue 2 (8th February 2023) - Gyawali, Siddinath; Pokhrel, Biraj; Uprety, Pratik; Gnawali, Arun
Abstract: An 83‐year‐old‐male patient presented with obstructive jaundice, whose imagings were consistent with the cholangiocarcinoma of the distal common bile duct. The tumor markers were within normal limits. IgG4 level was raised; therefore, IgG4‐sclerosing cholangitis was made as the provisional diagnosis. Steroid therapy was started to which he responded well. Abstract : IgG4‐sclerosing cholangitis should be considered as one of the differentials of suspected cholangiocarcinoma to prevent unnecessary surgical interventions.